(untitled) (Journal of Medical & Health Sciences Review, 2025)
A 43 year old male patient came to the department of Operative Dentistry at Islamic International Dental Hospital with a chief complaint of dull pain in upper left region from last 1 week and pain on biting. Clinical Examination revealed multiple carious lesions in the anterior and posterior dentitions of both the charges. Tooth #22 was tender to percussion and thermal testing gave a negative response. Peri apical radiograph showed and small radiolucency at the apical portion of #22 and also had an atypical anatomy in the coronal third of the tooth. A CBCT was carried out which indicated Dense Invaginatus type 2 Treatment options included, Extraction with replacement and non-surgical root canal treatment with post and core build up and crown lengthening followed by an extra coronal restoration. Patient was adamant to save the tooth so second option was chosen. Non-surgical root canal treatment and chemo mechanical treatment of the invagination using 3.5% NaOcl and 17% EDTA was carried out. The canal was obturated with single cone obturation technique and the invagination was filled with biodentine. Fiber post and composite core was done and ceremometal crown was given as the patient could not afford any other crown.